How Do Lecturers Implement Case and Project Learning Models to Strengthen the Merdeka Curriculum? : A Study at Tanjungpura University, Indonesia - Bistari, Bistari; Mumtazah, Nadia Wardah; Mardiyyaningsih, Asriah Nurdini; Rusdiono, Rusdiono (Universitas Pendidikan Mandalika, 2024)
This study explores how lecturers at Tanjungpura University implement case and project-based learning models to strengthen the Merdeka Curriculum. Employing a qualitative approach with a descriptive method, data were gathered from 49 lecturers across various faculties through questionnaires and unstructured interviews. Data analysis involved descriptive techniques, with questionnaire results analyzed by frequency and percentage, while interview responses were interpreted qualitatively to identify key themes. Findings indicate that while many lecturers have begun integrating case and project-based learning, the extent of implementation varies significantly among faculties. Significant challenges include a lack of awareness and understanding of these models, insufficient institutional support, and difficulty integrating these methods into theory-heavy or practice-oriented courses. However, factors such as the need to align teaching practices with accreditation standards and the availability of faculty development programs are essential enablers. The study concludes that case and project-based learning hold significant potential for enriching the Merdeka Curriculum, and more structured support and awareness-building initiatives are necessary to realize their full benefits. Recommendations for lecturers include improving competencies through training, collaborating in learning design, and developing evaluation methods. For policymakers, strengthening institutional support, socializing the curriculum, and reviewing policies to integrate case and project-based learning are advised.